Defendant Remorse and Publicity in Capital Trials: Is Seeing Truly Believing?. (December 2015) - Tallon, Jennifer A.; Daftary-Kapur, Tarika; Penrod, Steven
Exposure to negative pre-trial publicity (PTP) can bias jurors, but the role of PTP in capital sentencing remains unclear. The goal of this study was to examine how variations in PTP concerning a defendant's emotions prior to sentencing and variations in the defendant's emotions during sentencing influenced sentencing decisions. One hundred death-qualified community members served as mock jurors in a 2 (pre-sentencing publicity [PSP]: emotional vs. unemotional) × 2 (defendant's behavior at sentencing: emotional vs. unemotional) between groups factorial design. Participants were exposed to PSP approximately 1 week before viewing a DVD of a simulated sentencing hearing in which we manipulated the defendant's behavior. Appearing emotional during sentencing decreased the likelihood of a death sentence and improved evaluations of the defendant, but PSP exerted no effect on decision making. Attitudes toward the death penalty directly affected sentencing decisions and moderated the effects of both publicity and sentencing behavior.